PENAFSIRAN AYAT PERANG DAN DAMAI DALAM PERSPEKTIF MUHAMMAD QURAISH SHIHAB - Muhammad Ade Maulana Rokan (Studia Sosia Religia, 2021)
Abstract The war verses contained in the Koran essentially have a content and purpose for a purpose. Thus it is not appropriate to confront between the verses of peace and the verses of war. Some people misunderstand that the verses of war have invalidated the verses about peace. He also reminded that do not ever think that a Muslim is obliged to Islamize the whole world. The war to convert people to Islam never existed. The war is to defend religion, to defend belief in order to achieve peace. He emphasized that the war verse was basically aimed at peace. Therefore, if there is a war between the Muslims and other people and then ask for peace, then the Muslims must accept the invitation for peace. Keywords: War and peace